Safety climate and safety performance among the operatives at sime plantations sdn.bhd.gunung mas palm oil mill - 297110 Jivaratnam Ramasundaram; Hishamuddin Md. Som, supervisor (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Master of Management Technology) - Universiti Teknologi Malaysia, 2007